STUDI RESPON KAPASITAS PILAR BETON BERTULANG JEMBATAN TERHADAP BEBAN GEMPA HORISONTAL - Hilmansyah, Asep
To get stability of column structure, a single column of pier bridge generally have a big dimension exceeded strength capacity of section which is needed. In this thesis is studied about impact of a big column dimension to behavior of structure of bridge pier moment earthquake loads work. The method used is nonlinear static analysis where influence of design load of earthquake to a structure considered to be static loads which work at center of mass from each lump mass. Static load value is improved gradually until exceeded loading which induced the first yield happen in structure, then with the load increasing due to evolution of a big elastoplastic shape to reach the condition of crushing. The result in the form of capacity spectrum of bridge pier structure. This capacity spectrum was compared to demand spectrum of earthquake which to get of elastic response spectral displacement at location where the structure exist. The result of comparison between capacity spectrum with demand spectrum is performance point of structure which show structure respons to earthquake used. To get stress-strain distribution at element of pier column structure of bridge, structure was modeled as the three dimension element. In this case, concrete was modeled as element solid and reinforcement as the three dimension bar element. The arrangement of bar element applied as the discrite element at a long in surface of column. Analysis was done to the height change of pier at some reinforcement systems. Reinforcement systems determine variation of reinforcement quality and quantity which used. The result of spectrum capacity analysis got that for single column of reiforcement concrete pier of bridge at the time is happened of strong earthquake, the structure still in elastic condition so that not happened damage at pier column structure of bridge. Thereby, performance of pier column structure of bridge only measured level of maximum lateral deformation level. For the analysis of stress distribution at column base got that strength capacity concrete at column base smaller than stress block ekuivalen whitney capacity.